Fetal left ventricular non‐compaction cardiomyopathy with ascites: A case report. Issue 9 (10th July 2017) - Muraoka, Junsuke; Kodama, Yuki; Sameshima, Hiroshi; Michikata, Kaori; Matsuzawa, Satoshi; Masanao, Oohashi; Kaneko, Masatoki; Akaki, Mayumi; Sato, Yuichiro
Abstract: Here we report a case of fetal left ventricular non‐compaction cardiomyopathy with ascites and cardiac dysfunction at a gestational age of 34 +5  weeks. Laboratory tests did not reveal any sign of viral infection in utero . A female neonate weighing 2436 g was delivered by emergency cesarean section due to non‐reassuring fetal status. Postnatal echocardiography confirmed left ventricular non‐compaction cardiomyopathy with severe cardiac failure. Although she was treated effectively during the acute period by continuous flow peritoneal dialysis, surgical ligation of a patent ductus arteriosus, and inhaled nitric oxide, she died on day 41 of life. Symptoms of severe cardiac dysfunction appeared antenatally in this patient and the outcome was poor.